Development of a novel composite inhibitor modified with proanthocyanidins and mixed with ammonium polyphosphate. (15th December 2020) - Xue, Di; Hu, Xiangming; Cheng, Weimin; Yu, Xiaoxiao; Wu, Mingyue; Zhao, Yanyun; Lu, Yi; Pan, Rongkun; Niu, Huiyong; Hu, Shengyong
Abstract: Considering drawbacks such as the low inhibition efficiency and short inhibition life of an existing single physical and chemical inhibitor, a novel composite inhibitor (SAP-OPC-APP hydrogel) was developed. First, oligomeric proanthocyanidins (OPC) radicals were grafted and polymerized onto acrylic acid/sodium acrylate and then mixed with APP (ammonium polyphosphate). Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), free radical concentration analysis and thermogravimetric analysis (TGA) were adopted to analyze the inhibiting effect and mechanism of SAP-OPC-APP hydrogel. Research indicates that: (1) the added OPC reduced the number of easily-oxidized functional groups in coal: hydroxyl (-OH), methyl (-CH3 ), and methylene (–CH2 –) and increased the number of stable ether bonds (C–O–C); (2) after treatment with SAP-OPC-APP gel, the coal sample had a 62.83% reduction in heat release, 6.00% reduction in free radical concentration, and 13.93% enhancement of activation energy; (3) the graft co-polymerization of OPC with acrylate will increase the contact area between the grafted hydrogels and the surroundings, thus improving the water absorption capability of the hydrogel; Hence, irrespective of physical, chemical, and thermal stability aspects, the composite inhibitor manifested stable inhibitory effects during the entire process of spontaneous combustion of coal. Graphical abstract: Image 1 Highlights: Proanthocyanidins-grafted sodium acrylate crosslinked polymer resin. Composite inhibitor for entire oxidation process of coal. Elucidate fire-retardant mechanism of composite inhibitor.